COGNITIVE RESERVE AND DEMENTIA - Rodríguez Álvarez, Marina; Sánchez Rodríguez, Juan Luis (Anales de Psicología / Annals of Psychology, 2004)
According to demographic studies, 20-25% of the population of Spain will be elderly in 2020. This ageing of the population entails a notable increase in age-related diseases, including neurodegenerative processes. Cognitive Reserve has been suggested as the mechanism linking low levels of education with greater risk of neurodegenerative diseases. This reserve, the ability of the brain to better tolerate the effects of a pathology of dementia, may be the result of an innate gift or the effect of life experience, such as education or type of job. Other authors suggest the term brain reserve to refer to more passive ideas of reserve, based on characteristics of the individual such as brain size, number of neurons or synaptic density which help to compensate for possible degenerative diseases of the Central Nervous System. The aim of this work is to show all the possible variables supporting the theory of this hypothesis.